Direito à saúde no Brasil: Seus contornos, judicializaç\~ao ea necissiadade da macrojustiça - Fabiola Sulpino Vieira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– In Brazil, the right to health has achieved relevance in policy debate, especially in the last two decades, due to the increase in the number of lawsuits lawsuits against the executive branch to ensure access to medicines, exams, hospitalizations, among other goods and health services. The objective of this article is to discuss the effectiveness of this instrument, based on individual cases, as these decisions are made, in ensuring the right to health in the country. We conducted a narrative review of the technical-scientific literature and legal documents to determine the relevant issues at hand. Information on the distribution by population of public defenders and Ministry of Health financial resources allocated to comply with judicial orders and to finance the public health care system, known as SUS, is used to support our analysis. In addition, a flowchart was designed to try and grasp the rationality present in the set of guidelines approved during events promoted by the National Council of Justice (CNJ). We describe how the right to health is determined by Brazilian law, highlighting its recognition by the State as a fundamental human right and the extent of this right, which is in accordance with the social determination of the disease model as written in the Federal Constitution of 1988 (CF/1988). We show that, despite the advances promoted by SUS, large inequalities and inequities in health persist. We also present a panorama of the judicialization in health, aiming to demonstrate how individual demands have increased, discussing the positive and negative aspects of the current process and presenting the initiatives adopted to reduce these demands and the rationality behind the guidelines of the CNJ, which are intended to guide the work of magistrates in these matters. Some relevant issues that should be considered by the justice system when addressing these matters are discussed, arguing, finally, that the decisions made for individual cases, also known as microjustice, are important to ensure that all are treated equally by the state, under the conditions set in the policies. However, we argue that the judiciary should refrain from expanding their decisions to encompass health services not covered by the public system. We also argue that the Judiciary shoundn't lose sight of macrojustice in order to keep the formulation and implementation of public policies in this area, as well as macroeconomic policies, under control and ensure effectiveness to the right to health in Brazil.
Keywords: I18; 330; right to health; equity in access to health services; health status disparities; judicial decisions; judiciary; executive